Vaginal health and well ageing during all stages of women's life - Letteria Greco; Marco Fontana; Enzo Berardesca; Maurizio Barbieri Carones (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2020)
The genital area is becoming more and more the object of new attentions and targeted treatments are developed to support its functionality and beauty. The female world is closer to the awareness that the health of this intimate area should be considered an integral part of the beauty routine of every woman according to the new «well-ageing» approach. As face, hair and body are constantly exposed to hectic life, external agents and daily stress, even the vulvovaginal area suffers the consequences and the process of the physiological aging, modifying its tissue structures, leading to vulvovaginal dryness and irregular skin desquamation, loss of strength, elasticity, extensibility and density, loss of tissues brightness. A new approach, combining two ingredients, has been studied to improve vaginal wellness condition.